The Predatory State and Radical Politics: The Case of the Philippines - Christopher Ryan Baquero Maboloc (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2019)
This paper examines why the radical approach to politics of President Rodrigo Duterte, halfway into his term, has not overcome the predatory nature of the Philippine state. The predatory nature of the state implies that politics in the country is still defined by vested interests. The struggle of the Filipino is largely due to the structural nature of the injustices suffered by the country. Duterte’s brand of politics is antagonistic. The president is a polarizing figure. Despite the declaration that he will punish corrupt officials, traditional politicians and elite clans continue to rule the land with impunity. The country’s political ills are actually systemic. Elitism is rooted in colonial history that is perpetuated by an inept bureaucracy. It will be argued that the strong resolve and charisma of a leader is inadequate to remedy the troubles in fledgling democracies such as the Philippines.